Minimizing the Risk of Toxins in Staple Food Crops via Crossbreeding and Biotechnological Interventions - Veerendrakumar, H.V.; Shailaja, D.S.; Sagar, Nikhil U.; Bomireddy, Deekshitha; Mohinuddin, Khaja D; Naik, Yogesh Dashrath; Sudini, Hari Kishan; Guo, Baozhu; Liao, Boshou; Gangurde, Sunil S.; Pandey, Manish K. (Taylor & Francis Group, 2025)
Cereals and legumes are the major food and/or feed crops. The most dangerous risk to humans and animals is toxins that are present in agricultural products and their derivatives. Mycotoxins are produced by fungi and are highly toxic metabolites for animal and human health. The need for mycotoxin detection and control techniques is immense. This chapter provides an overview on types of mycotoxins present in maize and peanuts, their effect on animal and human health, management strategies, and the ways to minimize the toxins in these crops, as proof of concept, through crossbreeding and biotechnological tools. The focus must be to exploit multifunctional and multidimensional approaches of plant breeding and biotechnology to minimize the risk of mycotoxins contamination in food and feed crops.